Problems and Prospects of Information Interoperability of Academic Libraries in Central Asia - LAPO, P. M.; RAKHMATULLAEV, M. A. (University library at a new stage of social communications development, 2024)
Objective. The article is devoted to the analysis of the current state and prospects of information interoperability between academic libraries in Central Asia (CA). Methods. Publications on the topic of information and library interoperability, including in CA, have been studied, experience in the area has been analysed and summarized. Results. The authors proposed a comprehensive and systematic approach and methods to develop interoperability of academic libraries in CA. Conclusions. Summarizing the international experience of interlibrary cooperation at the regional level, it should be recognized that it is successful provided that there is a comprehensive approach to its provision, that is, the relevant bodies for planning, coordinating and monitoring information interoperability should be created and functioning, library personnel with relevant competencies should be trained and involved in the work, the relevant software and hardware and infrastructure should be available.